Repercussions of the use of probiotics in the treatment of chronic kidney disease - Luana Azevedo Dourado; Bianca Braga Gomes; Cainã Araújo Saraiva; Sandriny Maria de Almeida Oliveira; Sávio Benvindo Ferreira (Archives of Renal Diseases and Management - Peertechz Publications, 2023)
The dysbiotic microbiota is one of the clinical findings in patients with Chronic Kidney Disease (CKD), and this intestinal imbalance is associated with inflammation and oxidative stress. With this, probiotic supplementation presents itself as a possible adjuvant therapy to improve this dysbiosis, due to the contribution to the integrity of the intestinal barrier. In this context, this study aims to explain the relationship between the intestinal microbiota and CKD and the repercussions of the use of probiotics on the prognosis of these patients. For this, a narrative review was developed, using the LILACS, MEDLINE, Embase, and PubMed databases, in which articles available in full from the last 5 years, in Portuguese and English, were included. The indication of probiotics as a complementary therapy in renal patients was verified due to the disturbed intestinal microbiome, which aggravates the patient's inflammatory state. Thus, the supplementation of probiotics, such as Bifidobacterium longum, Lactobacillus rauteri LRE02, Lactobacillus rhamnosus GG, and Lactobacillus casei shirota, acts in the reduction of nephrotoxic substances derived from metabolism in the dysbiotic intestine, in the reduction of urea levels and creatinine levels, in addition to lower levels of C-reactive protein. Thus, the administration of probiotics has been shown to be a precursor in the modulation of toxins derived from the altered microbiota in these patients. On the other hand, there is still controversy about the use of this therapy, because despite improvements in biochemical manifestations, the effective impact on the preservation of glomerular filtration rate is still poorly understood.